Imaging the Growth of Recent Faults: The Case of 2016–2017 Seismic Sequence Sea Bottom Deformation in the Alboran Sea (Western Mediterranean). Issue 8 (12th August 2018) - Galindo‐Zaldivar, J.; Ercilla, G.; Estrada, F.; Catalán, M.; d'Acremont, E.; Azzouz, O.; Casas, D.; Chourak, M.; Vazquez, J. T.; Chalouan, A.; Sanz de Galdeano, C.; Benmakhlouf, M.; et al.
Abstract: The Eurasian‐African NW‐SE oblique plate convergence produces shortening and orthogonal extension in the Alboran Sea Basin (westernmost Mediterranean), located between the Betic and Rif Cordilleras. A NNE‐SSW broadband of deformation and seismicity affects the Alboran central part. After the 1993–1994 and 2004 seismic series, an earthquake sequence struck mainly its southern sector in 2016–2017 (main event M w = 6.3, 25 January 2016). The near‐surface deformation is investigated using seismic profiles, multibeam bathymetry, gravity and seismicity data. Epicenters can be grouped into two main alignments. The northern WSW‐ENE alignment has reverse earthquake focal mechanisms, and in its epicentral region recent mass transport deposits occur. The southern alignment consists of a NNE‐SSW vertical sinistral deformation zone, with early epicenters of higher‐magnitude earthquakes located along a narrow band 5 to 10‐km offset westward of the Al Idrisi Fault. Here near‐surface deformation includes active NW‐SE vertical and normal faults, unmapped until now. Later, epicenters spread eastward, reaching the Al Idrisi Fault, characterized by discontinuous active NNE‐SSW vertical fractures. Seismicity and tectonic structures suggest a westward propagation of deformation and the growth at depth of incipient faults, comprising a NNE‐SSW sinistral fault zone in depth that is connected upward with NW‐SE vertical and normal faults. This recent fault zone is segmented and responsible for the seismicity in 1993–1994 in the coastal area, in 2004 onshore, and in 2016–2017 offshore. Insights for seismic hazard assessment point to the growth of recent faults that could produce potentially higher magnitude earthquakes than the already formed faults. Key Points: The 2016–2017 seismic sequence is related to the wide NNE‐SSW sinistral fault zone located in the central part of the Alboran Sea Epicentral sea bottom deformations include mass transport deposits and recent faults Seismicity and sea bottom deformations are located west of the main Al Idrisi Fault, supporting the westward widening of the fault zone